2005
DOI: 10.1080/15434610590956921
|View full text |Cite
|
Sign up to set email alerts
|

“I Came to Prison to Do My Time — Not to Get Raped”: Coping Within the Institutional Setting

Abstract: The War on Drugs has yielded a significant growth in the United States prison population, particularly for women. A substantial percentage of women involved in the criminal justice system have a substance use disorder, have committed their crimes for drug money, or were convicted of a drug-related felony. Many druginvolved women enter prison with histories of sexual=physical assault and may be subjected to further victimization within the institution. Although staff sexual misconduct within women's prisons has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 26 publications
0
25
0
4
Order By: Relevance
“…Second, many of the studies had methodological limitations. There were several single‐case studies and case series, which were suggestive of negative effects on mental health, for example Ganser syndrome , PTSD and monosymptomatic hypochondriacal psychosis . These were excluded from data extraction because they are seen as weak evidence, and it is difficult to draw conclusions from them that can be reliably generalised.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many of the studies had methodological limitations. There were several single‐case studies and case series, which were suggestive of negative effects on mental health, for example Ganser syndrome , PTSD and monosymptomatic hypochondriacal psychosis . These were excluded from data extraction because they are seen as weak evidence, and it is difficult to draw conclusions from them that can be reliably generalised.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals living within this type of mesosystem are also often stigmatized and may have little chance of being believed if they report mistreatment. More specifically, prisoners often adapt or cope within this mesosystem with a de facto ''code of silence'' regarding abuse during incarceration in order to protect themselves from further stigmatization or longer confinement (Kubiak et al, 2005;Smith, 2001Smith, , 2005. This code of silence extends to reporting of abusive behavior by other inmates, which would be tantamount to snitching (Garland & Wilson, 2012).…”
Section: Reporting Sexual Assault In Prisons: Influencing Factors Acrmentioning
confidence: 99%
“…However, the significant changes observed in the alleviation of mental health symptoms and indirect aggression for this subsample of women are crucial, given these women's intensified risk factors, such as higher rates of suicide attempts and more extensive trauma histories than women without life sentences (Leigey & Reed, 2010). Previous research has also shown that women with long-term sentences often experience multiple forms of trauma before and during incarceration (e.g., Kupers, 1999;Kubiak, Hanna, & Balton, 2005), resulting in high rates of PTSD and making a significant decrease in PTSD symptoms for women with life sentences all the more notable. On the other hand, because women with life sentences were usually restricted from participat-ing in other therapeutic interventions, the lifers in the current study might have been highly motivated to take advantage of treatment opportunities, and therefore, experienced larger gains.…”
Section: Table 4 Group Difference Between Women With and Without A Dumentioning
confidence: 99%
“…Initial steps include a systematic process for problem identification, information gathering, and program design before moving toward pilot testing. We have reported extensively on these important developmental steps, including the underlying theoretical framework, curriculum development, and implementation feasibility, in an earlier paper (Kubiak, Fedock, Tillander, Kim, & Bybee, 2012). In brief, Beyond Violence (Covington, 2011), uses trauma theory (Herman, 1992(Herman, ,1997 as a foundation for the intervention with the basic tenant that early trauma influences both perceptions of and reactions to life events (Kendall-Tackett, 2000) and that exposure, particularly early or ongoing exposure, to traumatic events can result in not only repressed anger (Neumann, Houskamp, Pollock, & Briere, 1996;Newman & Peterson, 1996;Springer, Sheridan, Kuo, & Carnes, 2007) but also the use of alcohol and other drugs (Hedtke et al, 2008;Najavitis, Weiss, & Shaw, 1997).…”
Section: Beyond Violence: a New Intervention For Women With Violent Omentioning
confidence: 99%